Exploring the Ethnopharmaceutical Plants of Osing Tribe in Banyuwangi Regency: Potential Application for COVID-19 Therapy - Endah Puspitasari; Alfina Eka Damayanti; IntanNabila Sufi Zikrina; Dewi Dianasari (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 02-2021) [June 2021]